Hepatitis B virus reactivation associated with antirheumatic therapy: Risk and prophylaxis recommendations - Mori, Shunsuke; Fujiyama, Shigetoshi (World journal of gastroenterology : WJG, 2015)
Accompanying the increased use of biological and non-biological antirheumatic drugs, a greater number of cases of hepatitis B virus (HBV) reactivation have been reported in inactive hepatitis B surface antigen (HBsAg) carriers and also in HBsAg-negative patients who have resolved HBV infection. The prevalence of resolved infection varies in rheumatic disease patients, ranging from 7.3% to 66%. Through an electronic search of the PubMed database, we found that among 712 patients with resolved infection in 17 observational cohort studies, 12 experienced HBV reactivation (1.7%) during biological antirheumatic therapy. Reactivation rates were 2.4% for etanercept therapy, 0.6% for adalimumab, 0% for infliximab, 8.6% for tocilizumab, and 3.3% for rituximab. Regarding non-biological antirheumatic drugs, HBV reactivation was observed in 10 out of 327 patients with resolved infection from five cohort studies (3.2%). Most of these patients received steroids concomitantly. Outcomes were favorable in rheumatic disease patients. A number of recommendations have been established, but most of the supporting evidence was derived from the oncology and transplantation fields. Compared with patients in these fields, rheumatic disease patients continue treatment with multiple immunosuppressants for longer periods. Optimal frequency and duration of HBV-DNA monitoring and reliable markers for discontinuation of nucleoside analogues should be clarified for rheumatic disease patients with resolved HBV infection.